Cebu furniture design center - Basul, Danielle Anne T.; Yazon, Rizalino III O. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
Cebu-made furniture is known to be highly creative, innovative, and design-oriented. The high-quality exports of the Cebu furniture industry accounts for more than half of total furniture exports in the country, despite being only one of three main furniture manufacturing hubs in the country. Award-winning Cebuano designers have had major contributions towards the recognition of the Philippines as the "Milan of Asia". Despite these gains, the Cebu furniture industry is beset the problems. Locally, there is a need for design and market knowledge dissemination among firms. The lack of permanent showrooms also fail to attract domestic buyers. Workers, laborers, and craftsmen could also greatly benefit from upgrading their skills, and investing in more modern and efficient machinery and equipment. The establishment of an industry-focused furniture design center could help address the above problems. The establishment of an industry-focused furniture design center could help address the above problems. The purpose and intent of the Cebu Furniture Design Center is to at the forefront of "Cebu Branding", raise the standard of quality of furniture, develop and enhance the skills of laborers, enhance the Cebu furniture manufacturing cluster, encourage new businesses, make high-quality Cebuano furniture more accessible to the public, support local furniture shows and events, provide a hub for designers to meet and collaborate, and bring back a culture of artisanship and craftsmanship to the general community.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Furniture industry and trade -- Cebu City